2020
DOI: 10.25071/2291-5796.84
|View full text |Cite
|
Sign up to set email alerts
|

“Leaving no one behind”: COVID-19 Response in Black Canadian Communities

Abstract: Despite the universal healthcare system in Canada, Canadians of African Descent (CAD) still face numerous problems that place them at higher risk to pandemics such as COVID-19. From the struggles of working as frontline workers, to challenges compounded by pre-existing chronic medical conditions such as Diabetes, CAD may face unique issues, further weighing on their existing and potential health outcomes. This situation calls for closer attention to the specific needs of CAD who may be at greater risk of late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The evidence that Black immigrants with precarious immigration status are being left behind in HIV response due to lack of health coverage and universal and comprehensive access to healthcare calls for policy and program interventions within healthcare systems that are based on basic human rights, equity and social justice approach ( Etowa et al, 2020 ; McClarty et al, 2021 ). Our findings expand on a growing body of knowledge on legal and social determinants of health, demonstrating that immigration and health policies and extended state-level regulations intersect to affect immigrants’ access to HIV and treatment ( Caulford & Vali, 2006 ; Gostin, 2021 ; Martinez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that Black immigrants with precarious immigration status are being left behind in HIV response due to lack of health coverage and universal and comprehensive access to healthcare calls for policy and program interventions within healthcare systems that are based on basic human rights, equity and social justice approach ( Etowa et al, 2020 ; McClarty et al, 2021 ). Our findings expand on a growing body of knowledge on legal and social determinants of health, demonstrating that immigration and health policies and extended state-level regulations intersect to affect immigrants’ access to HIV and treatment ( Caulford & Vali, 2006 ; Gostin, 2021 ; Martinez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This scientific evidence informed the development of the UNAIDS 90-90-90 targets, which stated that by 2020, 90% of all people living with HIV will know their HIV status, 90% of people with an HIV diagnosis will receive ART, and 90% of people receiving ART will achieve viral suppression, and the Fast Track strategy which aimed to reduce incidences of HIV infection and end the epidemic by 2030 ( Cohen, 2011 ; UNAIDS, 2014a ). Despite biomedical advances and global initiatives aimed towards ‘ending HIV’, ACB immigrants in Ontario are being left behind in the HIV response due to inequities that restrict their right to health, including access to HIV healthcare and health-related services, leading to poor health outcomes ( Etowa et al, 2020 ; Mbuagbaw et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…People living in "ethno-cultural neighborhoods" in British Columbia had an ageadjusted COVID-19 mortality rate ten times higher than neighborhoods that were less than 1% visible minority (Subedi et al, 2020); and BIPOC populations living in Toronto made up 83% of reported COVID-19 cases (Cheung, 2020). There is also a significant correlation between high coronavirus death rates and low income, conditions of work, and visible minority status (Etowa et al, 2020), housing density (Yang & Aitken, 2021), and low levels of education and recent immigrant status (Wherry, 2020). The central problematic for this study is the social organization of HE discourses in the policymaking context, including the proliferation of the term HE in governmental and academic discourses amidst worsening health outcomes for marginalized and racialized Canadians.…”
Section: Narrative Contexts For Analyzing Hementioning
confidence: 99%
“…Countries around the world enacted public health measures to curtail the spread of the virus; lockdowns were imposed, in-person services were moved online, and individuals exposed to the novel coronavirus, along with any close contacts, were required to self-isolate. Individuals experiencing disparities in the social determinants of health (SDOH) were disproportionately impacted by the pandemic, with poorer health outcomes evident in marginalized and racialized communities (Etowa et al, 2020) Snowden & Graaf, 2020;Watson et al, 2020).…”
mentioning
confidence: 99%